Combining images with Photoshop Elements : - LoCascio, Ted (Wiley Publishing, Inc, 2006)
Combine your digital photos with an artist's flair and create dazzling composites, thanks to Photoshop Elements and this comprehensive guide from an industry expert. Using great photography and expert design sense, author Ted LoCascio clearly shows how it's done, from simple tasks such as swapping an image background, to more advanced ones such as creating an abstract photomontage.